Impacts of mega-events on destination competitiveness and corruption perception in South American countries - Thays Cristina Domareski-Ruiz; Adriana Fumi Chim-Miki; Edar Añaña; Francisco Antonio dos Anjos (Tourism & Management Studies)
Tourism destination competitiveness is a multidimensional concept that is widely studied in the academic literature. The corruption affects countries' business environment, generating negative image and barriers, so hindering its' ability to compete as a global player. This paper analyses this relation in the tourism industry in a sample of South American countries through a comparison within a five-year period based on the Travel and Tourism Competitiveness Index (TTCI) with the variation of Corruption Perception Index (CPI). An exploratory analysis to verify the upward and downward in these monitors was performed. The relation between TTCI and CPI was verified by a regression analysis. This research contributes directly to addressing a topic rarely explored in the tourism area, the influence of corruption perception in destination competitiveness. The results confirm that corruption perception impacts on tourism competitiveness of countries, but in presence of strong sources of tourism attractiveness, such as Mega events, this relation was reduced.